Mediating Role of Moral Identity in the Relationship between Ethical Leadership and Unethical Behavior of Employees: Evidence from the Oil and Gas Sector of Pakistan - Khan, Muhammad Kamran; Nazeer, Shakira (Journal of Management and Research, 2021)
This study draws on social identity, social learning, and trait-activation theories to probe if moral identity mediates the relationship between ethical leadership and unethical behavior. It investigates how ethical leadership serves as a predictor of employees’ unethical behavior and moral identity as a mediator between ethical leadership and employees’ unethical behavior. Together, these variables influence the self-reported unethical behavior of employees. The findings of this study are based on a sample of 297 oil and gas sector employees in Pakistan. For this purpose, data was analyzed through SPSS and AMOS. Consistent with trait-activation and social learning theories, employees on seeing their leaders behaving ethically develop a positive sense of the moral identity and report fewer incidences of unethical behavior. Furthermore, the findings suggested thatmoral identity and ethical leadership behavior are vital for predicting organizational outcomes. Thus, the originality of this study lies in the fact that it analyzed the influence of moral identity as a mediating variable.